2009
DOI: 10.1038/nature08195
|View full text |Cite
|
Sign up to set email alerts
|

miR-145 and miR-143 regulate smooth muscle cell fate and plasticity

Abstract: SUMMARY microRNAs are regulators of myriad cellular events, but evidence for a single microRNA that can efficiently differentiate multipotent cells into a specific lineage or regulate direct reprogramming of cells into an alternate cell fate has been elusive. Here, we show that miR-145 and miR-143 are co-transcribed in multipotent cardiac progenitors before becoming localized to smooth muscle cells, including neural crest stem cell–derived vascular smooth muscle cells. miR-145 and miR-143 were direct transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

72
1,412
5
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,429 publications
(1,524 citation statements)
references
References 42 publications
72
1,412
5
5
Order By: Relevance
“…Furthermore, studies have shown that miR-145 reduces cell viability in colon and cervical cancer cell lines after prolonged exposure (Shi et al, 2007;Schepeler et al, 2008;Wang et al, 2008). Finally, the expression of miR-145 has been shown to be induced by p53 (Sachdeva et al, 2009) and regulated by an enhancer element activated by SRF and Nkx-2 transcription factors (Cordes et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, studies have shown that miR-145 reduces cell viability in colon and cervical cancer cell lines after prolonged exposure (Shi et al, 2007;Schepeler et al, 2008;Wang et al, 2008). Finally, the expression of miR-145 has been shown to be induced by p53 (Sachdeva et al, 2009) and regulated by an enhancer element activated by SRF and Nkx-2 transcription factors (Cordes et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 50% of the known miRNAs are located within regions of genomic instability that are amplified or deleted in cancer (Calin et al, 2004), which may in part explain the aberrant expression observed. MIR145 is located at chromosome 5q32 in a putative bicistronic cluster with MIR143 (Cordes et al, 2009), a region commonly lost in myelodysplastic syndromes (Horrigan et al, 1996). miRNAs are predominantly transcribed by polymerase II and processed by Drosha into B70-100 nt precursor molecules (Lee et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR‐143‐3p (miR‐143) has an established role in the function of smooth muscle myoblasts and adipogenesis (Esau et al ., 2004; Cordes et al ., 2009; Elia et al ., 2009; Xin et al ., 2009). miR‐143‐5p is highly expressed in skeletal muscle tissue, and its expression is downregulated during aging (Kim et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, EC dysfunction and ageing‐related degenerative problems lie, at least in part, within the tissue‐specific released miRNAs 6, 15, 29, 50, 51, 80.…”
Section: Circulating Mirnas Associated With Myocardium Functionmentioning
confidence: 99%